Antibacterial activity of Lactobacillus species against some pathogenic and food spoilage bacteria - Sahu, Mamta (Food Biology, 2025)
The present study was conducted to examine the antimicrobial activity of different Lactobacillus species against pathogenic and food spoilage bacteria. Four species of Lactobacillus were isolated from homemade cheese, raw milk, dosa paste, sauce, and curd. Lactobacillus species isolated from the sampled food source include; Lactobacillus brevis, Lactobacillus plantarum, Lactobacillus fermentum, and Lactobacillus casei. The antimicrobial activity of L. plantarum (P2), L. brevis, L. plantarum (P1), L. casei, and L. fermentum was investigated against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Bacillus cereus using well diffusion method of the indicator isolate. The results reveal that the L. plantarum (P2) has highest inhibition zones towards E. coli (25.7±1.35 mm), S. aureus (27.6±0.94 mm), P. aeruginosa (24.4±1.05 mm), and B. cereus (04.2±0.17 mm). The lowest zones of inhibition towards the sampled pathogenic and food spoilage bacteria were reported by L. casei. Our results confirm that the L. plantarum (P2), L. brevis, L. plantarum (P1), L. casei, and L. fermentum had efficient antimicrobial inhibitory effect on E. coli, S. aureus, P. aeruginosa, and B. cereus. Thus these Lactobacillus species could be effectively used for the protection of food from different pathogenic and food Spoilage bacteria.